Effect of Polyamide (Nylon 6) Micro-Particles Incorporation into RTV Maxillofacial Silicone Elastomer on Tear and Tensile Strength - Fatihallah, Abdalbasit A.; Alsamaraay, Manar E. (Journal of Baghdad College of Dentistry, 2017)
Background: The longevity of any prosthesis depends on the materials from which it was fabricated, that is why, defects in the material properties may reduce the service life of prosthesis and necessitate its replacement. The aim of this study was to evaluate the effect of adding different concentrations of Polyamide-6 (Nylon-6) on the tear and tensile strength of A-2186 RTV silicone elastomer.Materials and Methods: 80 samples were fabricated by the addition of 0%, 1%, 3% and 5% by weight PA-6 micro-particles powder to A-2186 platinum RTV silicone elastomer. The study samples were divided into four (4) groups, each group containing 20 samples. One control group was prepared without PA-6 micro particles and three experimental groups were prepared with different percentage of PA-6 micro particles (1%, 3%, and 5%) by weight. Each group was further subdivided into 2 groups according to the conducted tests, i.e. tear and tensile strength tests (n=10). The data were analyzed with a descriptive statistical analysis, one-way ANOVA, post-hoc LSD test.Results: The mean value of tear and tensile strength of 1% PA-6 reinforcement group increased significantly when compared to control group on the contrast to the same values of 3% and 5% PA-6 reinforcement groups which were decreased significantly. Conclusion: the 1% PA-6 reinforcement improved tear as well as tensile strength among all other percentages (0%, 3% and 5%).